2023
DOI: 10.7547/23-015
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic Acid-Mediated Photodynamic Therapy on Wound Healing: A Systemic Review of Human Evidences

Jianhua Huang,
Hongwei Wang

Abstract: Backgrounds: Skin wounds are a kind of refractory disease frequently encountered in clinic, which brings enormous burden to patients. Great efforts to address the dilemma of wound healing have yielded some encouraging results, but they are still unsatisfactory. 5-aminolevulinic acid (ALA)-mediated photodynamic therapy (PDT) has been developed as a promising noninvasive treatment for skin wounds. A systematic review was performed to determine the existing evidence base for the clinical use of ALA-PDT on refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Photosensitizer Prodrug (5-Aminolevulinic Acid, Methyl Aminolevulinate) Photodynamic therapy (PDT), a therapeutically promising method that involves the combined action of photosensitizers, oxygen, and light, has emerged as a therapeutically promising method for treating a broad variety of solid tumors and infectious diseases. In treating skin scars, PDT stimulates wound healing by enhancing re-epithelialization and promoting angiogenesis, as well as modulating skin homeostasis [235]. In a recent review article, it was reported that PDT using 5-aminolevulinic acid (5-ALA) as a photosensitizer has been developed as a promising noninvasive treatment for skin wounds such as skin cancer, chronic leg ulcers, and erosive pustular skin diseases, in which 20% 5-ALA solution, a wavelength between 600 nm and 670 nm (red light), an energy density of 120 J/cm 2 , a frequency of once per week and three sessions were the most widely selected therapeutic parameters [236].…”
Section: Peripheral Vasodilator (Pentoxifylline)mentioning
confidence: 99%
See 1 more Smart Citation
“…Photosensitizer Prodrug (5-Aminolevulinic Acid, Methyl Aminolevulinate) Photodynamic therapy (PDT), a therapeutically promising method that involves the combined action of photosensitizers, oxygen, and light, has emerged as a therapeutically promising method for treating a broad variety of solid tumors and infectious diseases. In treating skin scars, PDT stimulates wound healing by enhancing re-epithelialization and promoting angiogenesis, as well as modulating skin homeostasis [235]. In a recent review article, it was reported that PDT using 5-aminolevulinic acid (5-ALA) as a photosensitizer has been developed as a promising noninvasive treatment for skin wounds such as skin cancer, chronic leg ulcers, and erosive pustular skin diseases, in which 20% 5-ALA solution, a wavelength between 600 nm and 670 nm (red light), an energy density of 120 J/cm 2 , a frequency of once per week and three sessions were the most widely selected therapeutic parameters [236].…”
Section: Peripheral Vasodilator (Pentoxifylline)mentioning
confidence: 99%
“…When PpIX is activated by visible red light, cytotoxic ROS and free radicals are generated. This phototoxic effect can cause malignant and non-malignant hyperproliferative tissue to be destroyed, decrease in size, and eventually disappear [235,237]. In addition, topical ALA-induced PDT stimulates wound healing by enhancing re-epithelialization, promoting angiogenesis, as well as modulating skin homeostasis [238].…”
Section: Peripheral Vasodilator (Pentoxifylline)mentioning
confidence: 99%